The implementation of value stream management in a company’s strategic and operational management - Vajna, István; Tangl, Anita Vajna Istvánné (REGIONAL AND BUSINESS STUDIES, 2011)
Many companies risk millions of dollars on technical developments and improvements without the guarantee of these investments’ sustainability. This means that development of strategic management has failed somewhere. Value Stream Management (VSM), implementing Value Stream Costing (VSC) is proving to be an effective strategic management philosophy, leadership structure, and set of tools to foster companies’ strategic sustainability. This article will discuss the whole practical approach to develop an eight-step strategic Value Stream Management System. The true value of the system consists in identifying 26 different transactional wastes, many more than are identified by the traditional lean approach, which identifies 7 main lean wastes in transactional processes. Using Value Stream Mapping in production and in the office can set up the full company operational strategy. The first step is the real current state. The next step is to analyze the data and the next major step is to setup the new Value Stream Analysis and Design (VSD) for all processes. This system can instantly react to the internal and external business environment changes. The system can eliminate the internal process’s wastes and can increase the company’s output and effectiveness. This leads to increased control of the drive of the company’s Quality Cost and Delivery. VSM is a modern lean management approach as well as the next opportunity in strategic and operational development for companies and the accounting system. Keywords: VSC, VSM, KAIZEN, Management system, TPM, 5S, PDCA, Controlling